Reflection on Environmental Sustainability Practices in University General Education Courses and Exploration of STEAM-6E Development Education - Shieh, Shiow-Fang (European Journal of Sustainable Development, 2025)
The sustainable vision based on low-carbon communities has illuminated the dream of rural estates in Taiwan's cities, and this beautiful blueprint has been implemented in May-uan Village, Douliu City. The themes of "environmental sustainability" and "community practice" are integrated into the university's general education curriculum. Qualitative research methods are used to collect data through literature analysis, observation, interviews, and teaching case data analysis. Through the cooperation and leadership of local volunteers and the emotional connection with students during service, we guide students to reflect on themselves, solve problems together as a team, and explore why environmental education requires holistic thinking and action. Secondly, the relevance of STEAM-6E development education and college students' participation in sustainable action is discussed. Finally, environmental education design suggestions from the perspective of college students are proposed to respond to the needs of many general education teachers to advocate environmental sustainability education and social and cultural environmental education in the future. Keywords: University general education courses; Holistic thinking; Community practice; STEAM-6E education; Sustainable vision